2010
DOI: 10.1016/j.jcin.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics of Culprit Atheromatic Plaque Are Associated With Coronary Flow After Thrombolytic Therapy

Abstract: The morphological characteristics of the culprit atheromatic lesion in patients with STEMI are associated with coronary flow after thrombolysis. The lipid content, the existence of rupture, and mainly the thickness of the fibrous cap are associated with the outcome of thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…Tanaka et al 15 showed by optical coherence tomography, that 67% of ruptured plaques in acute coronary syndrome patients possessed a fibrous cap thickness of <65 μm, whereas the remaining 33% had a rupture in a fibrous cap up to 140 μm in thickness. Toutouzas et al 16 demonstrated, also by optical coherence tomography, that fibrous cap thickness ranged from 30 to 140 μm in patients presenting with a ST elevation myocardial infarction treated with thombolytic therapy. In only 50.9% of patients did an optical coherence tomography-defined TCFA cause the infarct.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tanaka et al 15 showed by optical coherence tomography, that 67% of ruptured plaques in acute coronary syndrome patients possessed a fibrous cap thickness of <65 μm, whereas the remaining 33% had a rupture in a fibrous cap up to 140 μm in thickness. Toutouzas et al 16 demonstrated, also by optical coherence tomography, that fibrous cap thickness ranged from 30 to 140 μm in patients presenting with a ST elevation myocardial infarction treated with thombolytic therapy. In only 50.9% of patients did an optical coherence tomography-defined TCFA cause the infarct.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is not surprising as NIRS is most sensitive to cholesterol-rich, necrotic lesions with connective tissue degradation, the pathophysiologic substrate of both TCFAs and ThCFAs. 2,3 This inability to differentiate TCFAs from ThCFAs may take on less importance given the aforementioned clinical data suggesting that a plaque rupture causing an acute coronary syndrome 15,16 can occur in ThCFAs with fibrous caps up to 140 μm in thickness and evidence of a dynamic progression of ThCFAs to TCFA. 13 The current data showing increased markers of plaque instability in NIRS+ fibroatheromas is supportive and demonstrates that vascular inflammation is dynamic (ie, changes in NIRS positivity over time; Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…To focus on the culprit plaque morphology in ACS patients, intracoronary imaging modalities such as intravascular ultrasound (IVUS) [2,3,4], coronary angioscopy [2] and optical coherence tomography (OCT) [5,6,7,8,9,10,11] are currently used. The high image resolution and accurate tissue characterization in OCT makes this method particularly superior for detecting ruptured plaques and thin-cap fibroatheroma (TCFA), which is regarded as a rupture-prone plaque.…”
Section: Introductionmentioning
confidence: 99%
“…The high image resolution and accurate tissue characterization in OCT makes this method particularly superior for detecting ruptured plaques and thin-cap fibroatheroma (TCFA), which is regarded as a rupture-prone plaque. Differentiation between ACS patients with ruptured plaques and those without would be helpful for risk stratification because these pathogenic mechanisms affect the coronary flow after thrombolytic therapy [6] and infarct size [2,3,4]. However, performing intracoronary imaging examinations for all ACS patients is impossible in clinical practice because they are an invasive and time-consuming modality.…”
Section: Introductionmentioning
confidence: 99%
“…OCT is a light-based imaging modality able to visualize the majority of the morphological characteristics of the vulnerable plaque, including the type of plaque, the lipid core size, the exact thickness of the fibrous plaque [24,25], neovascularization and plaque infiltration by macrophages [26], and can also provide precise morphological assessment of the ruptured plaque and not only detect the presence and extent of thrombosis but characterize the type of thrombus as well [27,28,29]. The combined use of OCT and VH-IVUS has shown encouraging results [30], and further studies with the combined usage of these modalities are warranted.…”
Section: Invasive Imaging Modalitiesmentioning
confidence: 99%